Implementation of Decision Expert (DEX) in The “SALADGARDEN” Application - Anita Hidayati; Fityan Aula Juyuspan; Cindy Novianty; Muhammad Bima D S (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
In the field of agriculture, it is necessary to make right decisions for determining  various things. Among others is in determination of plants to be planted with several criteria such as knowledge, budget, land area, human resources, and investment value possessed. Therefore, decision support systems constitute appropriate method to facilitate farmers or non- farmers to make decisions. The expert system will be developed is desktop-based and uses Decision Expert (DEX) method to generate   recommendations   for   most   appropriate   decision selection therefore  it can be reference for all users. This  study will define criteria on value set of Salad Garden application in the DEX evaluation model. To be prepared for all possible combinations of input and output criteria values. Rules specified by decision maker with aggregation function declared point-by- point for all possible combinations of attribute values. From test results based on DEX method calculation, decision for plant species to be planted through determination of each criterion and rule.